Incest rape: Factor, impact and solution in the perspective of Islamic law - ABROR, K.; JALALUDDIN, A.; SYUKUR, I. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research aims at analyzing factors, impacts, and solutions to incest rape, according to the perspective of Islamic law. Uses a literature study as its methodologically approached. Incest rape is triggered by various factors. They include: (a) The absence of regular partners. (b) The secrecy of an incest relationship to its environs. (c) The implementation of moral values in the family. (d) A comforting feeling between close relatives. (e) Self-seclusion of the family (f) A protection of a family’s nobility. (g) cultural conflicts and poverty. Incest, or consanguinity cohabitation, also has negative impacts, either psychological, physical, or social. RESUMEN Esta investigación tiene como objetivo analizar factores y soluciones a la violación por incesto utilizando el enfoque de estudio de la ley islamica. Utiliza el estudio literario como enfoque metodológico. La violación por incesto es provocada por varios factores Incluyen: (a) La ausencia de socios regulares. (b) El secreto de una relación de incesto con sus alrededores. (c) la implementación de valores morales en la familia. (d) Un sentimiento de comodidad entre parientes cercanos. (e) Auto-reclusión de la familia (f) Una protección de la nobleza de una familia. (g) conflictos culturales y pobreza. El incesto, o convivencia de consanguinidad, también tiene impactos negativos, ya sean psicológicos, físicos o sociales.